No structure, no problem: Protein stabilization by Hero proteins and other chaperone-like IDPs - Lam, Andy Y.W.; Tomari, Yukihide; Tsuboyama, Kotaro (Biochimica et biophysica acta. General subjects, 2025)
In order for a protein to function, it must fold into its proper three-dimensional structure. Otherwise, improperly folded proteins are typically prone to aggregate through a process that is detrimental to cellular health. It is widely known that a diverse group of proteins, called molecular chaperones, function to promote proper folding of other proteins and prevent aggregation. In contrast, intrinsically disordered proteins (IDPs) lack substantial tertiary structures, but nonetheless serve important functional roles. In some cases, IDPs have been observed to display remarkably chaperone-like activities, where they stabilize the activities of client proteins and prevent their aggregation. While it was previously thought that chaperone-like IDPs were mainly utilized by extremophilic organisms in their survival of extreme stress, we recently showed that a group of chaperone-like IDPs, we named heat-resistant obscure (Hero) proteins, are also widespread in non-extremophile animals, including humans and flies. Thus, we should consider the possibility that IDPs serve significant chaperone-like functions in protein stabilization relevant to physiological conditions. However, as most of our understanding of how chaperones function is based on insights from their structured domains, it is unclear how chaperone-like IDPs elicit chaperone-like effects without these structures. Here we summarize our understanding of Hero proteins to date and, based on experimental evidence, outline the features that are likely important for their protein stabilizing activities. We draw on concepts from the studies of chaperones and chaperone-like IDPs, in order to draft potential models of how chaperone-like IDPs achieve chaperone-like effects in the absence of well-defined structures. [Display omitted] •IDPs in extremophiles are long known to have chaperone-like activities.•Hero proteins are chaperone-like IDPs widespread in non-extremophiles.•Hero protein activities depend on compositional properties and are context-dependent.•Models for the chaperone-like effects of IDPs are discussed.